Trade, Factor Proportions, and Political Rights - Tavares, José (The Review of Economics and Statistics, 2008)
This paper uses aggregate data to test the implication that capitalpoor individuals favor trade liberalization in poor (capital-scarce) countries and are against it in rich (labor-scarce) countries. Income per capita is used as a proxy for the country capital-labor ratio while political rights is used as a proxy for the capital-labor ratio of the median voter. We analyze the determinants of average tariff rates in a cross section of countries to find that they are negatively associated with both income per capita and political rights, while they are positively, significantly, and robustly associated with their interaction, corroborating our initial hypothesis.